Exploring the influence of psychological factors on the comorbidity of dental caries and obesity in adolescents from the perspective of the oral-gut-brain axis - Wang, Meng; Yang, Xiaopeng; Li, Yimin; Jiang, Mingxin; Chen, Bairu; Yang, Wei; Ma, Nan; He, Shili; Wang, Chengyue (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThis study investigates how psychological factors influence the comorbidity of dental caries and obesity in adolescents through the oral-gut-brain axis. Adolescence is a critical period for both physical and psychological development, yet dental caries and obesity are prevalent issues that can negatively impact mental health. The study aims to provide insights into the underlying mechanisms and potential prevention and treatment strategies.MethodsAn epidemiological survey was conducted on 1,024 students aged 12–15 from Beizhen No. 1 Junior High School. A total of 90 adolescents were selected for biosample research. The methods used included 16S rRNA gene sequencing, untargeted metabolomics, and SourceTracker analysis to examine oral and gut microbiota and metabolite concentrations.ResultsSignificant differences in oral and gut microbiota and metabolite concentrations were found among adolescents with different health statuses. Adolescents with caries and obesity showed distinct microbial profiles compared to healthy controls. The study also identified potential oral and gut microbial biomarkers associated with psychological disorders. SourceTracker analysis revealed a higher rate of ectopic colonization of oral microbiota in the intestines of adolescents with caries and obesity.DiscussionThe study highlights the roles of the oral-gut and oral-brain axes in the comorbidity of dental caries and obesity among adolescents. The findings suggest that oral and gut microbiota play crucial roles in disease progression, and their imbalances may affect mental health through the oral-gut-brain axis. The results provide a theoretical foundation for developing integrated intervention strategies targeting both oral and systemic health.